Design and Synthesis of 3-Substituted Indolin-2-one Derivatives with Methyl (E)-2-(3-Methoxy)acrylate Moiety - Luo, Xi; Zhang, Yi-Ying; Wang, Yu-Liang (Asian Journal of Chemistry, 2015)
In this article, fifteen indolin-2-one derivatives with methyl (E)-2-(3-methoxy)acrylate group were designed and synthesized. The structures of target compounds were confirmed by 1H NMR, IR and HR-MS spectra analysis.